Status of Brazilian research on microplastics present in aquatic ecosystems: freshwater - Rani-Borges, Bárbara [UNESP]; Martins, Thaís F. G. [UNESP]; Pompêo, Marcelo (My University, 2021)
Microplastics are small fragments of polymers. Due to their size (0.1 μm to 5 mm), they may pollute various natural resources, such as air, soil, and water bodies. There are few studies focusing on the relation between microplastics and freshwater ecosystems in the world. In Brazil, the situation is quite similar to the rest of world: data are scarce and reveal little about the real dimension of this anthropogenic phenomenon. In view of the relevance of this topic for the scientific community, the present review aims to trace the state of the Brazilian research so far, and point out the research gaps in the area, such as the lack of research with sediment samples, and results regarding the toxicity of secondary microplastics, which are more common in the environment than the primary ones. A bibliographic survey was conducted in online databases to identify all scientific articles published in Brazil until December 2020. Eighteen articles were found and analyzed. We concluded that the number of articles has shown a significant increase, mainly in 2020, with scientific productions very relevant for the academic community. However, greater investments and incentives are still needed to consolidate the development of this research area in Brazil.
Keywords: Brazil; Plastics; Pollution; Water